Artificial Intelligence in Notarial Practice: Legal Risks and Ethical Considerations: Kecerdasan Buatan dalam Praktik Kenotariatan: Risiko Hukum dan Pertimbangan Etis - Dine Maharani; Danang Dwi Cahyo Oktarianto (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The accelerating integration of Artificial Intelligence (AI) into legal services has raised pressing questions about the duties, authority, and ethical boundaries of the notarial profession. This study analyses the legal risks and ethical considerations associated with the use of AI in notarial practice, focusing on the Indonesian normative framework. Using a normative juridical method with statutory, conceptual, and doctrinal approaches, this research examines the Notary Office Act (UUJN), the Electronic Information and Transactions Act (UU ITE), the Personal Data Protection Act (UU PDP), and related regulations alongside scholarly literature on AI and law. The findings show that AI cannot be classified as a legal subject because it lacks the capacity to bear rights and obligations; instead, it functions as a legal object or technological tool whose operation remains under human control. While AI may improve efficiency in document drafting, identity verification, and archival management, its uncritical adoption threatens the principles of physical presence, personal authority, evidentiary value of authentic deeds, and notarial accountability. The study concludes that comprehensive regulatory reform and an updated code of ethics are required so that AI strengthens rather than displaces the notarial profession in the digital era.